Comparative Study of The Phenomenon of Trance and Possession Based on Western Perspective and Islamic Psychology - Bahari, Lalu Pradipta Jaya; Saadah, Nurus; Harry, Rannikko; Baron, Gregory (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
The phenomena of trance and possession are events that occur in various cultures and traditions. In general, both phenomena are characterized by the loss of control of one's body or consciousness. However, views on the causes and treatment of both phenomena may vary between Western and Islamic Psychology perspectives. This study aims to compare Western and Islamic Psychology perspectives on the phenomena of trance and possession. From the Western perspective, the phenomenon is often explained as a medical or psychological condition that can be treated with scientific methods such as drugs and psychological therapies. Whereas in Islamic Psychology, the phenomenon is explained as a manifestation of supernatural powers that affect a person's mental state. This research combines a comparative qualitative and descriptive approach by analyzing literature related to the phenomena of trance and trance from both perspectives. The results show that although there are differences in views between the two perspectives, both recognize the influence of psychological factors in the occurrence of these phenomena. In addition, Islamic Psychology recognizes the existence of supernatural powers that influence the phenomenon of trance and trance-inducing, while the Western perspective tends to reject this view. In conclusion, this study provides an understanding of the differences in views between the Western perspective and Islamic Psychology regarding the phenomena of trance and possession. It also shows that although the views between the two perspectives may differ, they can complement each other and provide a more holistic understanding of the phenomenon.